Analysis method of urban formation in relation to buildings of historical value: Case Study in Crissiumal/RS - Bertaluci, Gabriela Luiza Leismann; Neckel, Alcindo; Silva, Thaísa Leal da (National Journal of City Management, 2022)
The formation process of cities happens due to the migratory movements that contributed to the colonization of Brazil, and is also responsible for leaving an architectural heritage of great historical and cultural importance for the future of humanity. The objective of this review is to analyze the urban insertion of the first historical and culturally valued buildings in the city of Crissiumal, located in the state of Rio Grande do Sul (Brazil), in order to understand how they influenced the urban formation. For this, initially, the first buildings built in the city were identified, and then their insertion and their influences in relation to the formation of the urban fabric were analyzed. The research presents an analysis of maps in relation to the macro parceling, through the relationship between full and empty spaces, based on the proposal of the Inventory of Configurations of Urban Spaces - INCEU. Through research and analysis carried out from the maps created, it was possible to perceive that the buildings implanted in the immediate surroundings of Praça 25 de Julho had an influence on the urbanization and formation of the city. These buildings housed important places for society, such as City Hall, Church, Schools and Commerce. In this way, most of the new homes were built close to these places, and the city expanded from this environment.